CEO Narcissism, Tax Aggressiveness, and The Role of The Audit Committee: Evidence from Mining Companies in Indonesia (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This study aims to analyze the effect of CEO narcissism on tax aggressiveness moderated by audit committee size. The population in this study are mining sector companies listed on the Indonesia Stock Exchange (IDX) during 2019 to 2021, totaling 58 companies. Purposive sampling, the chosen sampling technique, yielded 31 companies and a total of 155 observations. This study uses secondary data, namely financial statements and annual reports, and uses documentary techniques to collect research data. We used panel data regression analysis as the data analysis technique and conducted hypothesis testing using the Eviews v.12 application. The results of this study indicate that CEO narcissism influences tax aggressiveness, and audit committee size can affect the relationship between CEO narcissism and tax aggressiveness.